Synergistic anxiolytic efficacy exploring the combined effects of diazepam and zinc chloride in wistar albino rats - Naik, Vishwani V.; Desai, Vedita Hegde; Noronha, Sam (Drug Research, 2024)
Combinations of medications are frequently employed when their effects are similar. Beyond aiding in the reduction of medication dosages, this approach may yield additional positive outcomes. Studies have shown that zinc can mitigate anxiety-related behavior in laboratory animals. This study aimed to investigate the potential stabilizing effects of zinc chloride and diazepam in Wistar albino rats.Five groups, each comprising six animals. Test groups included two combinations of zinc chloride and diazepam, each with two different doses of diazepam (1 and 2 mg/kg) and 10 mg/kg of zinc chloride. Four established anxiety models—the Elevated Plus Maze (EPM), the hole board, the light and dark box, and the mirror chamber—were employed to assess the anxiolytic effects. The combination of zinc chloride and diazepam proved to be more effective than the individual doses of zinc chloride and diazepam, indicating enhanced anxiolytic effects.
Keywords: elevated plus maze; synergism; hole board; light and dark; zinc; anxiety